NEO-COLONIALISM AND THE DEVELOPMENTAL CHALLENGES OF POST-COLONIAL AFRICA - Olawale Olufemi Akinrinde; Samuel Oyewole (The Republic of Indonesia Defense University, 2021)
Liberal political economists typically ascribe the reasons, natures, and dynamics of development and security in the global South, including Africa, Asia, and Latin America, to internal deficiencies. As a result, among other things, weak institutions, policy deficits, ethnicity, corruption, bad leadership, and all other signs of an entity in desperate need of salvation have been recognized as dangers to the corporate existence and survival of African and other developing countries. While the decolonization of African and other developing countries has provided impacted peoples a sense of political belonging, the historical processes required to promote these nations' economic potential have been weakened. As a result, the capacity of postcolonial states to chart their development paths and reinvent themselves has been malignly berated, denied, and frustrated by neo-colonialist aspirations, strategies, and actions, those who had grudgingly and dishonestly foisted cancerous independence on the entire continent of Africa and other Third World regions. Relying, as it should, given the qualitative nature of the study, the study assesses the implications of the neo-colonial legacies for Nigeria's development aspiration.